Detecting the Car Number Plate Using Segmentation (International Journal of Engineering and Computer Science, 2014)
The number plate recognition system is one kind of an Intelligent Transport System. The proposed work is used to extract numbers from the number plate. This technology is used in various security purposes for finding stolen cars, traffic management system, in electronic toll collection, smuggling of cars, usage of cars in terrorist attacks and illegal activities. This work is based on edge detection and efficient morphological operations. Character segmentation is the process of extracting the characters and numbers from the license plate. Noises in the image are removed using filtering techniques. Optical Character Recognition (OCR) technique is used for the character recognition. In OCR the filtering character is matched with template using template matching algorithm and finally the character is extracted.